Islam in Southeast Asia : Political, Social and Strategic Challenges for the 21st Century (Book collections on Project MUSE., 2017)
This book looks at Islam and its strategic implications for Southeast Asia. Part I outlines Islamic doctrine and traces the history and growth of Islamic economic institutions in the region. In Part II, politics, governance, civil society and gender issues are examined in the context of Southeast Asian Islam. Part III devotes itself to the impact of modernization and globalization on Muslim society. Part IV examines and evaluates the impact of the 2001 terrorist attacks on the icons of the American superpower. The Conclusion offers some perspectives on the challenges and prospects for Islamic doctrine and practice in the context of Southeast Asia.